ANALYSIS OF THE FINANCIAL REPORT OF PT ROYAL PRIMA TBK BASED ON FINANCIAL RATIOS FOR THE PERIOD 2020–2024 - Musowafah (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The abstract should briefly describe the purpose of the research, research methods, main findings, and implications. The abstract must be written in a single paragraph and should not exceed 200 words. This study aims to analyze the financial condition and performance of PT Royal Prima Tbk for the 2020–2024 period using horizontal analysis and financial ratio analysis, including liquidity, solvency, and profitability ratios. The results show that the company’s financial condition fluctuated annually. Revenue increased in 2021, declined in 2022, and increased again during 2023–2024. High operating costs caused profits to decrease, resulting in losses in 2023 and 2024. Overall, the company was still able to meet its shortterm obligations and maintained a relatively safe capital structure, but its profitability remained weak, indicating the need for better cost efficiency and asset management.